2001
DOI: 10.3133/ofr00513
|View full text |Cite
|
Sign up to set email alerts
|

National Irrigation Water Quality Program data-synthesis data base

Abstract: Under the National Irrigation Water Quality Program (NIWQP) of the U.S. Department of the Interior, researchers investigated contamination caused by irrigation drainage in 26 areas in the Western United States from 1986 to 1993. From 1992 to 1995, a comprehensive relational data base was built to organize data collected during the 26-area investigations. The data base provided the basis for analysis and synthesis of these data to identify common features of contaminated areas and hence dominant biologic, geolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Selenium concentrations in tissues are reported on a wet‐weight basis. Selenium concentrations in eggs expressed on a wet‐weight basis can be converted to approximate dry‐weight concentrations based on previous reports that rainbow trout eggs contain 61% moisture [14]. Where this calculation is used in the discussion, concentrations are reported as calculated wet weight.…”
Section: Methodsmentioning
confidence: 99%
“…Selenium concentrations in tissues are reported on a wet‐weight basis. Selenium concentrations in eggs expressed on a wet‐weight basis can be converted to approximate dry‐weight concentrations based on previous reports that rainbow trout eggs contain 61% moisture [14]. Where this calculation is used in the discussion, concentrations are reported as calculated wet weight.…”
Section: Methodsmentioning
confidence: 99%
“…These studies determined that little or no measurable amount of these metals were transferred to or accumulated in eggs. Additionally, Schwarzbach et al [50] summarized data from Seiler and Skorupa [51] that reported on silver concentrations in more than 1000 wild bird eggs. Schwarzbach et al [50] suggested that silver can, but rarely will, accumulate in avian eggs.…”
Section: Discussionmentioning
confidence: 99%
“…DeForest et al (1999) assumed that whole‐body tissue had a moisture content of 75%, while ovaries were assumed to have a moisture content of 85%. Holm (2002) assumed that rainbow trout eggs contain 61% moisture based on 3 rainbow trout egg samples with moisture contents ranging from 59.4% to 62.5% (Seiler and Skorupa 2001); Barrett et al (2001) found that average rainbow trout egg moisture contents ranged from 55.6% to 67.0%. Differing assumptions regarding moisture content of fish tissues, such as those previously, introduce unnecessary uncertainty and controversy.…”
Section: The Decision‐making Frameworkmentioning
confidence: 99%